PERAN SERTIFIKASI HALAL DALAM MENINGKATKAN KEPERCAYAAN KOSUMEN PADA PRODUK YOUGHURT RUMAH BABE KOTA BENGKULU - Nadya Fristia (LPPM STAI Muhammadiyah Probolinggo, 2026)
This consider points to decide the part of halal certification in expanding buyer believe in Rumah Babe yogurt items in Bengkulu City, to get it shopper discernments of halal certification in Rumah Babe yogurt items, and to recognize the foremost prevailing components in building customer believe. This ponder utilized a subjective investigate strategy with a expressive approach. The witnesses in this ponder were 10 buyers chosen utilizing purposive inspecting. Information collection methods were conducted through in-depth interviews, perception, and documentation. The comes about show that halal certification plays a noteworthy part in expanding buyer believe in Rumah Babe yogurt items in Bengkulu City. Shoppers see halal certification as a ensure of item security, cleanliness, and compliance with halal standards. Halal certification is the foremost prevailing calculate in building shopper believe, compared to other variables such as taste and bundling. With halal certification, buyers feel more certain and comfortable expending Rumah Darling yogurt items.